Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2021)
It is my immense pleasure to share with you the first 2021 issue of Studies in Second Language Learning and Teaching. It brings together five papers reporting the findings of empirical studies as well as two reviews of very recent publications. The issue opens with the contribution by Mariusz Kruk, Mirosław Pawlak, and Joanna Zawodniak, who investigate changes in the levels of boredom experienced by 13 Polish university students majoring in English during four EFL classes as well as factors responsible for such fluctuations. Multiple sources of data were applied which included boredom-grids, where participants indicated the intensity of this negative emotion on a 7-point Likert scale at 5-minute intervals, class evaluation forms, narratives, semi-structured interviews with four students after each class, and lesson plans. A combination of quantitative and qualitative analysis demonstrated that boredom was indeed subject to between- and within-class variation, which resulted from various constellations of variables, with repetitiveness, monotony and predictability playing a key role. In the second paper, Xiaowan Yang and Mark Wyatt report a qualitative case study which examined teachers’ beliefs about learners’ motivation and their own motivational practices, and the actions they actually took in this respect in the classroom in the context of teaching English for Specific Purposes (ESP) in China. The analysis of the data collected from three university-level teachers of business English by means of pre-observation interviews, in-class observations and stimulated recall interviews yielded evidence for tensions between participants’ cognitions and practices they engaged in, showing that such mismatches negatively affect their self-determination. The existence of this cognitive disharmony is attributed to scarce opportunities for professional development, outdated knowledge about motivation and cultural influences. The theme of ESP also features in the following paper by Cailing Lu, Frank Boers and Averil Coxhead, who explored understanding of technical terms included in a list of technical words related to Traditional Chinese Medicine (TCM) with the aim of determining which of these terms should be emphasized during instruction. The requisite data were collected by means of a word association task, drawing on Read’s (1998) Word Association Test, as well as retrospective interviews from 21 BA students in China and New Zealand. The analysis showed that although the students manifested good understanding of the targeted items, especially high-frequency ones, some Chinese participants experienced difficulty understanding mid- and low-frequency words. By contrast, the Western learners mainly struggled with Chinese loan words, but their comprehension was not impacted by cultural differences. In the fourth paper, Bryła-Cruz reports the findings of a study which looked into the role of gender in the perception of English segments by Polish learners of English as a foreign language. The data were collected from 40 male and 40 female secondary school students who were asked to indicate the sound they heard in 20 sentences containing minimal pairs. The differences between males and females failed to reach statistical significance for most targeted segments and while the hierarchy of perceptual difficulty was not identical for both groups, it was similar, which suggests that differences between the sound systems of the first and second language might trump the mediating role of gender. In the final paper, Jesús Izquierdo, Silvia Patricia Aquino Zúñiga, and Verónica García Martínez shift the focus to the context of foreign language education in rural schools in southeast Mexico, zooming in on the challenges faced by generalist teachers, or non-language specialists, tasked with the job of teaching English. The data were collected by means of questionnaires administered to 155 such teachers in 17 schools and semi-structured interviews with those who manifested the greatest involvement in professional development. Using frequency analysis and categorical aggregation, the researchers show that generalist teachers are confronted with a wide array of problems related to their professional preparation, instructional techniques used as well as the sociocultural realities of L2 instruction in rural communities. In addition, only a few teachers are prepared to develop professionally, relying instead on limited strategies that help them combat the challenges they encounter. The issue also includes two book reviews by Jarosław Krajka and Mirosław Pawlak. The first book deals with the assessment of English proficiency among young learners while the second is devoted to research into learning and teacher psychology from the perspective of complex dynamic systems theory (Larsen-Freeman & Cameron, 2007). I am hopeful that all the contributions will provide food for thought to our readers and inspire them to further disentangle the intricacies of second language learning and teaching.